2013
DOI: 10.1161/circimaging.112.000159
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Dimensions in Febrile Children Without Kawasaki Disease

Abstract: Conclusions-This pilot study found that mean CA dimensions in children with non-KD febrile illnesses are larger than those in normative afebrile subjects but smaller than dimensions in patients with KD. Future studies should augment the available data on CA dimensions in children with more severe febrile illnesses. (Circ Cardiovasc Imaging. 2013;6:239-244.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 17 publications
2
52
1
4
Order By: Relevance
“…The coronary artery abnormalities associated with KD can be differentiated from lesser degrees of dilation that may be rarely present with other febrile illnesses. 95 The prevalence of coronary artery abnormalities in a clinical trial of initial treatment was 23% at 4 weeks after enrollment, reduced to 8% with 4 infusions of low-dose IVIG. 126 In a subsequent trial of single high-dose IVIG, this was further reduced to ≈4%.…”
Section: Coronary Artery Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coronary artery abnormalities associated with KD can be differentiated from lesser degrees of dilation that may be rarely present with other febrile illnesses. 95 The prevalence of coronary artery abnormalities in a clinical trial of initial treatment was 23% at 4 weeks after enrollment, reduced to 8% with 4 infusions of low-dose IVIG. 126 In a subsequent trial of single high-dose IVIG, this was further reduced to ≈4%.…”
Section: Coronary Artery Abnormalitiesmentioning
confidence: 99%
“…However, it is unclear whether such reductions in dimensions represent resolution of inflammatory changes in the arterial walls or hemodynamic or functional factors related to fever and circulating inflammatory mediators. 95,96 by guest on http://circ.ahajournals.org/…”
Section: Coronary Artery Abnormalitiesmentioning
confidence: 99%
“…A small sized pilot study reported that coronary artery dimensions in patients with febrile illness other than KD were significantly larger than in the afebrile normative population, but smaller than in KD patients. 17 The pathogenesis of coronary artery dilatation remains unknown in febrile disease states, but may be related to higher myocardial oxygen demand caused by fever and tachycardia. The subsequent increase in coronary blood flow results from compensatory dilation of the coronary arterys.…”
Section: Resultsmentioning
confidence: 99%
“…24 Clínicamente, se constata taquicardia sinusal, 25 precordio activo por miocarditis, ritmo de galope y soplo regurgitativo de insuficiencia mitral. Ocasionalmente, bajo gasto cardíaco y shock por disfunción ventricular grave.…”
Section: Evaluación Cardiológica 71 Manifestaciones Cardiovascularesunclassified
“…En caso de que este último fuera normal, el tercer ecocardiograma deberá realizarse entre las 6 y las 8 semanas desde el inicio de la EK. 12,25,31 En los pacientes en los que se detecta la presencia de aneurismas coronarios, derrame pericárdico, insuficiencia valvular, disfunción ventricular o persistencia de signos de inflamación, el ecocardiograma debe repetirse, al menos, semanalmente para evaluar si hay progresión de las complicaciones mencionadas. 12 La evaluación ecocardiográfica de las arterias coronarias debe ser lo más completa posible e incluir la CI, la DA, la CX, la CD, segmentos proximal, medio y distal, y la DP.…”
Section: Ecocardiogramaunclassified